The Difficulty of ASEAN Decision Making Mode on South China Sea Dispute: The ASEAN Charter Perspective - Limsiritong, Nattapat; Springall, Apiradee; Rojanawanichkij, Onkanya (Asian Political Science Review, 2019)
This article is written from the perspective of the ASEAN Charter to explain the difficulty of ASEAN decision making mode on South China Sea dispute by examining ASEAN Charter. It expresses that the main difficulty of ASEAN to decide the case of South China Sea dispute is the decision-making mode of ASEAN under Article 20(1) of ASEAN Charter which based on consultation and positive consensus. This dispute has separated ASEAN into two groups such as (1) Group of parties into a dispute which consisted of Brunei, Malaysia, Indonesia, Philippines, and Vietnam, and (2) Group of non-parties into a dispute consisted of Thailand, Singapore, Lao PDR, Myanmar, and Cambodia. It is difficult in practice for ASEAN Summit to make a decision based on Article 20(1) and get consensus because ASEAN Summit is composed of the heads of state of each Member State who generally take decisions based on political interests of their own, not interest of ASEAN as the whole. Article 20(1) itself creates the lockdown by the fact that the group of non-parties into dispute tried to avoid the conflict between People’s Republic of China (PRC) and the group of parties into dispute due to prevent their national interest more than ASEAN’s interest. Hence the author proposes ASEAN to revise the decision-making mode of ASEAN under Article 20(1) of ASEAN Charter or apply another way of decision-making modes such as majority vote or negative consensus (reverse consensus) for ASEAN Summit instead of consultation and positive consensus.